HUBUNGAN PENGETAHUAN GIZI, ASUPAN PROTEIN DAN ZAT BESI, STATUS GIZI DENGAN KADAR HEMOGLOBIN PADA REMAJA PUTRI - Setyaningrum, Yahmi Ira Setyaningrum; Achmad, Alya Nabilah; Sutjiati, Endang (Pendidikan Biologi Universitas PGRI Ronggolawe Tuban, 2024)
The nutritional problem that young women are currently susceptible to is anemia. Anemia is caused by low hemoglobin levels, menstruation in adolescent girls, nutritional status, lack of food intake containing protein and iron, infections, low nutritional knowledge, and others. This study aims to analyze the relationship between nutritional knowledge, protein and iron intake, and nutritional status with hemoglobin levels in young women at SMAI Kepanjen. The research method uses a Spearman correlation analytical survey with a cross sectional approach. The population in this study was all class XI female students at SMAI Kepanjen totaling 106 people with a sample of 56 people. The sampling technique uses simple stratified random sampling. The results of the Spearman correlation statistical test analysis show that there is a relationship between nutritional knowledge and hemoglobin levels (p= 0.003), there is a relationship between protein intake and hemoglobin levels (p = 0.000) and iron intake and hemoglobin levels (p = 0.039) while there is a relationship between status. nutrition on hemoglobin levels (p = 0.000). It is hoped that young women can increase their knowledge and gain insight into nutrition by providing education in collaboration with nutritionists at the Kepanjen Community Health Center and SMAI Kepanjen and consuming blood supplement tablets simultaneously with SMAI Kepanjen students once a week and supervised by UKS teacher.